2021
DOI: 10.1108/jeee-08-2020-0300
|View full text |Cite
|
Sign up to set email alerts
|

Passive but defiant: the role of innovative capabilities in knowledge management and corporate entrepreneurship

Abstract: Purpose This paper aims to examine the role of organizational innovative capabilities (OIC) on the relationship between knowledge sharing (KS), corporate entrepreneurship (CE) and firm performance (FP). Specifically, this study uses the knowledge-based view to develop a model that examines the mentioned relationship. Design/methodology/approach Using survey data from 520 participants across 75 service sector companies in Thailand, measurement and structure models are tested through structural equation modeli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 111 publications
0
10
0
Order By: Relevance
“…, 2012). According to the natural resource-based view (NRBV) of the firm (Hart, 1995), environmental investments facilitate the development of competitive advantage, and such competitive advantages, according to stakeholder theory can translate into improved financial performance if effective relationship management with key stakeholders is in place (Khalil et al ., 2021).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…, 2012). According to the natural resource-based view (NRBV) of the firm (Hart, 1995), environmental investments facilitate the development of competitive advantage, and such competitive advantages, according to stakeholder theory can translate into improved financial performance if effective relationship management with key stakeholders is in place (Khalil et al ., 2021).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…The significance of loadings and path coefficients was investigated via bootstrapping. "Bootstrapping is a nonparametric method in which subsamples are generated with randomly derived observations from the original sample" (Khalil et al, 2021). For the student survey also the measurement model was examined for reliability and validity and then the analysis was conducted using simple statistics since only one section of a larger survey is being considered here.…”
Section: Data Analysis and Resultsmentioning
confidence: 99%
“…Various authors have drawn attention to the organizational mechanisms that allow entrepreneurial firms to access and apply knowledge, including trust (De Clercq et al ., 2013), human resource practices (Mustafa et al ., 2013), networks (Turner and Pennington, 2015), transactive memory system (Batra et al ., 2021), role of top management (Martín-Rojas et al ., 2013) and individual-level mechanisms such as motivation and psychological ownership (Pittino et al ., 2018). Our review revealed that entrepreneurial orientation affects how knowledge is created and shared in an organization (for example, Latif et al ., 2021; Keh et al ., 2007; Khalil et al. , 2022).…”
Section: Thematic Areas Of Researchmentioning
confidence: 99%